The Liminal Epistemology of Apocalyptic Disability in August Wilson’s Joe Turner’s Come and Gone and Fences - Atieh, Majda (Latakia University Journal - Arts and Humanities Sciences Series, 2017)
This article highlights the African American reconfiguration of the conventional Apocalyptic perception of disability in two plays by August Wilson, Joe Turner’s Come and Gone (1988) and Fences (1987). Wilson’s focal plays present a flexible adaptation of Apocalyptic disability that counteracts cultural absolutism. They highlight the effaced role of African reality in proposing liminality as a valid epistemology to destabilize the presumed pattern that shapes the traditional Apocalypse. So, Wilson’s dramaturgy visualizes an Apocalyptic disability that maintains a liminal construction, being a projection of various social and cultural experiences, a missing gap in Wilson’s scholarship. Ultimately, I address the cultural context where disability and African culture intersect to free the subjugated pathologized black other from dominant imperial paradigms.